Effectiveness of The Rural Community Health Practice Carried Out In Nabweru Sub-County, Wakiso District. - Shafic Kiberu; Sulaiman Mahmood Kakooza (Student's Journal of Health Research, 2021)
Background: The field report was about the effectiveness of the rural community health practice to prove whether it's viable to the people in the community. The Objectives of the study were to gain more practical experience in the field, to acquire more knowledge in environmental health, to put theoretical knowledge into practice, and to enable the community to practice proper sanitation and hygiene. The field study was carried out in approximately two months from 16th|/July/2014 to 5th/September/2014. Methodology I reported at the organization on 17th July 2014 and was received by the District Health Inspector who later introduced him to the office public department.  I received orientation in the office of the District Health Inspector for about a week and then later was sent to the sub-county for the rest of the period.  I was assigned to the public health department of the Nabweru sub-country in the Wakiso district Results and observations The Organizational Structure of the Nabweru sub-country was fully understood. I learned better ways of how to deal with the community in many aspects. Skills gained Included Communication and Immunization. Problems encountered included those from the organization, the workers, and trainees.  Conclusion and recommendation The rural community practice was important as it helped to relate what was taught in class to the practical aspect. Therefore I acknowledge the role played by the staff of Nabweru Sub-County and the community at large. The sub-county in conjunction with the district should budget for sensitization outreaches in the community.